The areas will be in the ratio 1 : 1.5^2 = 1 .2.25
The area will be larger by a factor 2.25.
Answer:
x=6
AC = 28
Step-by-step explanation:
4x+4= AC
4x +4 = 14 + 3x -4
4x-3x= 14-4-4
x = 6
AC = 4(6) +4 = 24+4 = 28
Answer:
x=2
Step-by-step explanation:
Solution is attached
You can plug 2 back into the equation to verify :)
<h3>
Answer: 5</h3>
=========================================================
Explanation:
Vertex form is
y = a(x-h)^2 + k
We are told the vertex is (3,-2), so we know (h,k) = (3,-2)
y = a(x-h)^2 + k will update to y = a(x-3)^2 - 2
--------
Then we also know that (x,y) = (4,3) is a point on the parabola. Plug those x and y values into the equation and solve for 'a'
y = a(x-3)^2 - 2
3 = a(4-3)^2 - 2
3 = a(1)^2 - 2
3 = a - 2
3+2 = a
5 = a
a = 5
This is the coefficient of the x^2 term since the standard form is y = ax^2+bx+c.
I will give you everything I can do:
11)
Lets say Car A travels at x mph. That means Car B travels at x+2 mph.
Both of them are traveling towards each others, so we can say the total speed is 2x+2.
Now i takes 3 hrs and we know the distance.
Since R*T=D
Then 3(2x+2)=270
So 2x+2=90
2x=88
x=44
12)
To find perpendicular we want to find the opposite reciprocal of the original slope. Therefore the slope is 3/2.
Now we must find the equation of the line with the given variable.
First find b.
5=3/2*4+b
b = -1
So the equation of this line is:
y=3/2x-1
13) All work will be shown below.
6-3(-2-4x)=2(3(x-4)+7)
6+6+12x=2(3x-12+7)
12+12x=2(3x-5)
12+12x=6x-10
6x=-2
x = -1/3
14)
First we must find the amount each train traveled.
The speed of F train(Freight train)=x
The speed of P train(passenger train)=x+6
Their combined speed is 2x+6
It takes 2 hrs to cover 100 miles
So 2(2x+6)=100
2x+6=50
2x=44
x=22
So the freight train covered 44 miles and the passenger train covered 56 miles.
To find average speed you must do Total Distance/Total Time.
44/2 and 56/2
Which are 22 and 28.
The average speed of F train is 22 mph and average speed of P train is 28 mph.
15) Again opposite reciprocal.
3/5 -> -5/3
Work:
-4=-3*-5/3+b
-4=5+b
b=-9
y = -5/3x-9
16)
F=kx-kx0
First kx0 = 0
So F=kx
So x=F/k